2019
DOI: 10.1002/ccd.28545
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of the drug‐eluting bioresorbable magnesium scaffold compared with polymeric scaffolds and a permanent metallic drug‐eluting stent

Abstract: Objectives: To compare on the bench the physical and mechanical properties of Magmaris, a magnesium bioresorbable scaffold (BRS), with Absorb and DESolve polymeric BRS and a permanent metallic stent. Background: Understanding the mechanical and physical properties of BRS is crucial for appropriate implantation and postdilatation. Methods: Testing was performed in fluid at 37 C and in silicone bifurcation phantoms with a 30 angle between main branch (MB) and side branch. Results: The 3.0-mm Magmaris BRS did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
(60 reference statements)
0
15
0
Order By: Relevance
“…Reports regarding optical coherence tomography (OCT) and bench comparison of nBVS with eBVS showed that eBVS has fewer peaks per hoop (6 vs. 9), smaller vessel coverage (“footprint”; 27% vs. 30%), and higher radial strength than the nBVS (1.3 atm vs. 1.1 atm) while nBVS provided smaller residual area stenosis (20.1% vs. 14.9%; p < 0.01) and larger maximum (3.2 mm vs. 3.5 mm; p = 0.01) and minimum (2.7 mm vs. 2.9 mm; p < 0.01) scaffold diameters with no strut fracture, suggesting better expansion of the nBVS [ 12 , 13 ]. Another bench test comparing Magmaris (Biotronik AG, Bülach, Switzerland), Absorb and DESolve BVS showed that Absorb and Magmaris have larger recoil rates and only DESolve did not fracture during side branch dilatation and mini-kissing balloon postdilatation [ 14 ]. In our study, QCA analysis showed larger post-procedure minimum lumen diameter (MLD) in the nBVS group despite similar baseline angiographic RVD measured in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Reports regarding optical coherence tomography (OCT) and bench comparison of nBVS with eBVS showed that eBVS has fewer peaks per hoop (6 vs. 9), smaller vessel coverage (“footprint”; 27% vs. 30%), and higher radial strength than the nBVS (1.3 atm vs. 1.1 atm) while nBVS provided smaller residual area stenosis (20.1% vs. 14.9%; p < 0.01) and larger maximum (3.2 mm vs. 3.5 mm; p = 0.01) and minimum (2.7 mm vs. 2.9 mm; p < 0.01) scaffold diameters with no strut fracture, suggesting better expansion of the nBVS [ 12 , 13 ]. Another bench test comparing Magmaris (Biotronik AG, Bülach, Switzerland), Absorb and DESolve BVS showed that Absorb and Magmaris have larger recoil rates and only DESolve did not fracture during side branch dilatation and mini-kissing balloon postdilatation [ 14 ]. In our study, QCA analysis showed larger post-procedure minimum lumen diameter (MLD) in the nBVS group despite similar baseline angiographic RVD measured in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Biodegradable magnesium (Mg) and its alloys are ideal candidates for stent platforms because they have less neointimal formation and provide long-term inhibition of the growth of smooth muscle cells (SMCs), unlike stainless steel [5,6]. The Mg alloys also have twice the tensile strength of unmodified biodegradable poly-l-lactide (PLLA), which leads to flexible stenting deployment and better radial force [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the dependency of expansion and eccentricity seems to be primarily a problem associated with the Absorb BVS ( 25 ) rather than the DESolve BRS ( 26 ). Barkholt et al ( 27 ) performed a bench evaluation of the mechanical properties of the Magmaris BRS and compared them with those of DES and PLLA-based BRS. They demonstrated that the Magmaris was more resistant to strut fracture than the Absorb BVS.…”
Section: Discussionmentioning
confidence: 99%